Framing Digital Ethics in Participatory Media: A Qualitative Analysis of the AI Face-Swap Challenge on TikTok - Okviosa, Audhiandra; Gunarian, Nathalia; Novianty, Suci Marini; Arrianie, Lely (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study investigates how ethical concerns surrounding AI face-swapping are framed in digital discourse, using the case of the viral TikTok Face Swap Challenge. While such content is often perceived as playful and innovative, it raises significant issues related to consent, identity manipulation, and platform accountability. Employing Entman’s (1993) framing theory, this qualitative research analyzes user-generated TikTok videos, Indonesian and international media coverage, and expert interviews to explore how different actors construct meaning around this emerging technology. Using thematic framing analysis, the study identifies four dominant frames: (1) Innovation as Disruption, which celebrates novelty and creativity while minimizing risks; (2) Consent and Deepfake Risk, which highlights ethical concerns around impersonation and agency; (3) Ethics as Afterthought, reflecting how users and platforms sideline moral reflection for engagement; and (4) Platform Responsibility, which shifts focus to systemic enablers of virality without accountability. These frames often intersect, revealing the complex ways that ethical meaning is negotiated across participatory and institutional actors. The findings contribute to framing theory by extending its application to social media ecosystems, where users, media, and experts co-construct public narratives. The study also highlights the ethical vacuum often left by rapid innovation and offers practical implications for digital governance, media literacy, and algorithmic accountability. By mapping how public discourse shapes ethical understanding, this research underscores the urgent need for frameworks that balance technological advancement with robust moral consideration in platform-based communication